Knowledge sharing and affective commitment: the mediating role of psychological ownership. Issue 6 (12th October 2015) - Li, Jian; Yuan, Ling; Ning, Lutao; Li-Ying, Jason
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the meditating role of psychological ownership which includes both organisation-based psychological ownership (OPO) and knowledge-based psychological ownership (KPO) on the relationship between affective commitment and knowledge sharing. Design/methodology/approach – This paper is an empirical study based on structural equation modelling, with a sample of 293 employees from 31 high-technology firms in China. Findings – The result indicated that affective commitment had a significant positive effect on OPO but no effect on KPO; OPO was positively related to both common and key knowledge sharing, while KPO exerted a negative impact on both; common knowledge sharing was positively related to key knowledge sharing; the relationship between affective commitment and key knowledge sharing was multi-mediated by OPO and common knowledge sharing. Originality/value – OPO and KPO play an essential role in transferring the effect of employees' affective commitment to common knowledge sharing and key knowledge sharing, which unravels the blackbox of how effective commitment affects knowledge sharing.